2014
DOI: 10.7863/ultra.33.7.1193
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Findings in Total Anomalous Pulmonary Venous Return

Abstract: The diagnosis of TAPVR can be suspected on standard axial views included in second-trimester obstetric screening examinations of the fetal heart and confirmed on fetal echocardiography with the use of pulsed wave Doppler imaging. Clues recognizable on obstetric sonographic screening have the potential to contribute to increasing the diagnostic yield for prenatal detection of TAPVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…TAPVR is rare, with an incidence of 0.6–1.2 per 10 000 live births . Antenatal diagnosis is restricted by the limited ultrasonographic clues that raise suspicion of possible TAPVR . For this reason, it is crucial to consider critical cardiac lesions in sick newborns despite having a normal antenatal course.…”
Section: Discussionmentioning
confidence: 99%
“…TAPVR is rare, with an incidence of 0.6–1.2 per 10 000 live births . Antenatal diagnosis is restricted by the limited ultrasonographic clues that raise suspicion of possible TAPVR . For this reason, it is crucial to consider critical cardiac lesions in sick newborns despite having a normal antenatal course.…”
Section: Discussionmentioning
confidence: 99%
“…In non-heterotaxy cases, TAPVC can be detected as an isolated anomaly or with other complex heart/great vessel lesions such as atrioventricular septal defect, transposition of the great arteries, pulmonary stenosis, double outlet right ventricle, and coarctation of the aorta. When TAPVC is diagnosed through prenatal echocardiography, a trend of more fetuses accompanied with heterotaxy syndrome or complex CHD and less fetuses with isolated TAPVC has been noted [ 24 ]. TAPVC genetic etiology is remaining vogue and previous study reported some possible disease-driven genes (e.g., ACVRL1, SGCD , 4p13-q12, ANKRD1 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…An inability to demonstrate this normal connection is an important sign for suspecting TAPVC. Recent studies have described this as the first clue to suspect the disease [ 7 , 24 ]. A smooth posterior wall of the LA can be viewed as an accessory feature to this abnormal connection of PVs and is observed in some cases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations